Increasing liana frequency in temperate European forest understories is driven by ivy. Issue 10 (5th October 2020) - Perring, Michael P; De Frenne, Pieter; Hertzog, Lionel R; Blondeel, Haben; Depauw, Leen; Maes, Sybryn L; Wasof, Safaa; Verbeeck, Hans; Verheyen, Kris; ,
Abstract : The increasing prevalence of woody liana species has been widely observed across the neotropics, but observations from temperate regions are comparatively rare. On the basis of a resurvey database of 1814 (quasi‐)permanent plots from across 40 European study sites, with a median between‐survey interval of 38 years, and ranging from 1933 (earliest initial survey) to 2015 (most recent resurvey), we found that liana occurrence has also increased in the understories of deciduous temperate forests in Europe. Ivy ( Hedera helix ) is largely responsible for driving this increase across space and time, as its proportional occurrence has grown by an average of 14% per site. Enhanced warming rates, increased shade, and historical management transitions explain only some of the variation in ivy frequency response across the dataset, despite surveys coming from across continental gradients of environmental conditions. Uncovering the mechanisms underlying ivy expansion, and the potential consequences for forest structure and functioning, requires further research. Given the magnitude of increases in understory ivy frequency and its possible impacts, scientists, policy makers, and resource managers must be mindful of the patterns, processes, and implications of potential "lianification" of temperate forests.